PENGARUH AMBON CITY OF MUSIC TERHADAP CITRA DIPLOMATIK INDONESIA: STUDI PADA PARTISIPASI INDONESIA DALAM FESTIVAL MUSIK INTERNASIONAL - Farhan Afipudin Wasahua; Devita Prinanda; Shannaz Mutiara Deniar (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2025)
This study examines the influence of Ambon City of Music on Indonesia's diplomatic image through participation in various international music festivals. The main focus of this study is how Ambon's status as a UNESCO City of Music contributes to strengthening Indonesia's cultural diplomacy on the global stage. The purpose of this study is to analyze the role of music as an instrument of public diplomacy and to identify the impact of international music activities on the world's perception of Indonesia. The scope of the study includes cultural diplomacy activities involving Ambon in the UNESCO creative city network and its participation in various international music festivals in the 2019–2024 period. The method used is a descriptive qualitative approach with data collection through literature studies, sand analysis of cultural diplomacy policy documents. The results show that Ambon City of Music plays a role as an effective symbol of Indonesia's soft power in strengthening national identity through music and opening opportunities for cross-cultural collaboration. Indonesia's participation in international music festivals has been proven to increase global exposure and strengthen Indonesia's positive image as a cultured, creative, and peaceful country. Thus, the Ambon City of Music initiative has a significant contribution to Indonesia's cultural diplomacy by establishing an inclusive, dynamic, and sustainable diplomatic image.